Comparison of Upper Extremity Function After Operative and Non-operative Management of Distal Radius Intra-Articular Fractures with Clinical Assessment of QuickDASH Score - Istiqomah, Ridnia Nur; Wiria Aryanta; Erial Bahar (Sriwijaya Journal of Surgery, 2024)
Introduction: Intra-articular fracture of the distal radius is a common injury and can disrupt upper extremity function. This study aims to compare upper extremity function after treatment of intra-articular distal radius fractures in productive age between operative and non-operative procedures using the QuickDASH score. Methods: This observational analytical study with a retrospective cohort design involved 80 patients with intra-articular distal radius fractures who were managed operatively (60 patients) and non-operatively (20 patients) at Dr. Mohammad Hoesin General Hospital Palembang. Data was collected from patient medical records and analyzed using the independent t-test and Chi-Square test. Results: The mean QuickDASH score in the operative group (10.53 ± 17.25) was significantly lower than the non-operative group (23.29 ± 23.82) (p = 0.012). There was a significant relationship between operative management and QuickDASH score (p = 0.023). Patients treated operatively were 1.5 times more likely to have normal upper extremity function (QuickDASH score ≤ 20). Conclusion: Operative treatment of intra-articular distal radius fractures in productive age provides better upper extremity functional outcomes compared to non-operative treatment, based on QuickDASH score assessment.